2020
DOI: 10.1038/s41598-020-60988-2
|View full text |Cite
|
Sign up to set email alerts
|

Going Beyond Rate Changes as the Sole Indicator for Dynamic Triggering of Earthquakes

Abstract: Remote earthquake triggering is a well-established phenomenon. Triggering is commonly identified from statistically significant increases in earthquake rate coincident with the passage of seismic energy. in establishing rate changes, short duration earthquake catalogs are commonly used, and triggered sequences are not typically analyzed within the context of background seismic activity. Using 500 mainshocks and four western USA 33-yearlong earthquake catalogs, we compare the ability of three different statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 54 publications
1
19
1
Order By: Relevance
“…Intriguingly, our observed triggering rate (over 20%) is significantly larger than the triggering rate documented in Pankow and Kilb (2020), which also examined the possible triggering cases in Anza, California (SJFZ‐I). They found that remote dynamic triggering is rare (<2%) by examining 500 triggering earthquakes and four 33‐year‐long earthquake catalogs in the Western US.…”
Section: Discussioncontrasting
confidence: 74%
See 4 more Smart Citations
“…Intriguingly, our observed triggering rate (over 20%) is significantly larger than the triggering rate documented in Pankow and Kilb (2020), which also examined the possible triggering cases in Anza, California (SJFZ‐I). They found that remote dynamic triggering is rare (<2%) by examining 500 triggering earthquakes and four 33‐year‐long earthquake catalogs in the Western US.…”
Section: Discussioncontrasting
confidence: 74%
“…One possible explanation for the higher triggering rate in this study is the magnitude of completeness (M c ) of the QTM catalog. The nominal M c of the QTM catalog is 0.3, which is almost one magnitude smaller than the M c of the catalogs analyzed in Pankow and Kilb (2020). For example, our statistical procedure would suggest that the 2012 Haida Gwaii earthquake did not dynamically trigger microearthquakes in Southern California within 24 h of its occurrence, when only using earth-FAN ET AL.…”
Section: Remote Dynamic Triggering Ratesmentioning
confidence: 80%
See 3 more Smart Citations